Effect of a strategy of comprehensive vasodilation versus usual care on health‐related quality of life among patients with acute heart failure. (6th August 2021) - Belkin, Maria; Wussler, Desiree; Gualandro, Danielle Menosi; Shrestha, Samyut; Strebel, Ivo; Goudev, Assen; Maeder, Micha T.; Walter, Joan; Flores, Dayana; Kozhuharov, Nikola; Lopez‐Ayala, Pedro; Danier, Isabelle; et al.
Abstract: Aims: We aimed to assess the long‐term effect of a strategy of comprehensive vasodilation versus usual care on health‐related quality of life (HRQL) among patients with acute heart failure (AHF). Methods and results: Health‐related quality of life was prospectively assessed by the generic 3‐levelled EQ‐5D and the disease‐specific Kansas City Cardiomyopathy Questionnaire (KCCQ) among adult AHF patients enrolled in an international, multicentre, randomised, open‐label blinded‐end‐point trial of a strategy that emphasized early intensive and sustained vasodilation using maximally tolerated doses of established oral and transdermal vasodilators according to systolic blood pressure. Changes in EQ‐5D and KCCQ from admission to 180 day follow‐up were individually compared between the intensive vasodilatation and the usual care group. Among 666 patients eligible for 180 day follow‐up, 284 (43%, median age 79 years, 35% women) and 198 (30%, median age 77 years, 35% women) had completed the EQ‐5D and KCCQ at baseline and follow‐up, respectively. There was a significant improvement in HRQL as quantified by both, EQ‐5D and KCCQ, from hospitalization to 180 day follow‐up, with no significant differences in the change of HRQL between both treatment strategies. For instance, 39 (26%) versus 33 (25%) patients had an improvement by at least one level in at least two categories in the EQ‐5D. Median increase in KCCQ overall summary score (KCCQ‐OSS) was 17.6 (IQR 2.0–42.6) in the intervention group versus 18.5 (IQR 3.9–39.3) in the usual care group ( P < 0.001 vs. baseline, P = 0.945 between groups). Conclusions: Among patients with AHF, long‐term HRQL quantified by EQ‐5D and KCCQ improved substantially, with overall no significant differences between a strategy of comprehensive vasodilation versus usual care.